Abnormal Fractional Amplitude of Low-Frequency Fluctuation as a Potential Imaging Biomarker for First-Episode Major Depressive Disorder: A Resting-State fMRI Study and Support Vector Machine Analysis - Gao, Yujun; Wang, Xi; Xiong, Zhenying; Ren, Hongwei; Liu, Ruoshi; Wei, Yafen; Li, Dongbin (Frontiers in Neurology, 2021)
Objective Major depressive disorder (MDD) is one of psychiatric disorders with serious negative health outcmoes, however, there is no reliable method of diagnosis. This study was to explore the clinical diagnostic value of fractional amplitude of low-frequency fluctuation (fALFF) based on the support vector machine (SVM) method for diagnosis of MDD. Methods A total of 198 first-episode MDD patients and 234 healthy controls were involved in this study, and all participants received the resting-state functional magnetic resonance imaging (fMRI) scanning. Imaging data were analyzed with the fALFF and SVM methods. Results Compared with the healthy controls, the first-episode MDD patients showed higher fALFF in the left mid cingulum, right precuneus and left superior frontal gyrus (SFG). The increased fALFF in these three brain regions were positively correlated with the ECRT, and the increased fALFF in left mid cingulum and left SFG were positively correlated with the HRSD-17 scores. The SVM results showed that increased fALFF in the left mid cingulum, right precuneus and left SFG exhibited high diagnostic accuracy of 72.92% (315/432), 71.76% (310/432) and 73.84% (319/432), respectively. And the highest diagnostic accuracy of 76.39% (330/432) was demonstrated for the combination of increased fALFF in the right precuneus and left SFG, along with a sensitivity of 84.34% (167/198), and a specificity of 70.51% (165/234). Conclusion Increased fALFF in the left mid cingulum, right precuneus and left SFG may serve as neuroimaging marker for first-episode MDD. The use of the increased fALFF in the right precuneus and left SFG in combination showing the best diagnostic value.